Sesquiterpene lactones and cancer: new insight into antitumor and anti-inflammatory effects of parthenolide-derived Dimethylaminomicheliolide and Micheliolide - Li, Jian; Li, Xin; Liu, Hongwei (Frontiers in Pharmacology, 2025)
The isolation and application of biological macromolecules (BMMs) have become central in applied science today, with these compounds serving as anticancer, antimicrobial, and anti-inflammatory agents. Parthenolide (PTL), a naturally occurring sesquiterpene lactone derived from Tanacetum parthenium (feverfew), is among the most important of these BMMs. PTL has been extensively studied for its anticancer and anti-inflammatory properties, making it a promising candidate for further research and drug development. This review summarizes the anticancer and anti-inflammatory effects of PTL and its derivatives, with a focus on Micheliolide (MCL) and Dimethylaminomicheliolide (DMAMCL). These compounds, derived from PTL, have been developed to overcome PTL’s instability in acidic and basic conditions and its low solubility. We also explore their potential in targeted and combination therapies, providing a comprehensive overview of their therapeutic mechanisms and highlighting their significance in future cancer treatment strategies.